IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH DEMONSTRATION METHOD OF THE CLASS XI IPS 1 STUDENTS OF SMA MUHAMMADIYAH 1 PALEMBANG - Waliyani, Waliyani; Yuliani, Sri (English Community Journal, 2018)
Improving Students’ English Speaking Skills Through Demonstration Method of The class XI IPS 1 students  of SMA Muhammadiyah 1 Palembang. This study aims to improve the students’ speaking skills of class XI IPS 1 at SMA Muhammadiyah 1 Palembang by using the demonstration method. The subject of this research is all the students of class XI IPS1 of SMA Muhammadiyah Palembang consisting of 32 students. This study used descriptive qualitative and quantitative methods in which the data contained in this study are numbers, percentages and depictions used to determine the success or failure of a study. The research instrument was in the form of daily tests and interview. The data obtained from the instrument that shows students who reached the KKM on: (1) Pre-test are 3 students (9.37%), (2) the result of  Cycle I is 7 students (21.87%), (3) the result of cycle II is 17 students ( 53.12%), and (4) the result of Cycle III is 25 students (78.12%). From the data can be concluded that the application of the demonstration method can improve students’ speaking skills of class XI IPS 1 studens of  SMA Muhammadiyah 1 Palembang.